A study of an improved cutting mechanism of composite materials using novel design of diamond micro-core drills. (January 2015) - Butler-Smith, P.W.; Axinte, D.A.; Daine, M.; Kennedy, A.R.; Harper, L.T.; Bucourt, J.F.; Ragueneau, R.
Abstract: Core drilling at small diameters in carbon composite materials is largely carried out using diamond electroplated tools consisting of hollow shafts and simplistic geometries that are likely to work in an abrasional/rubbing mode for material removal. The paper reports a step change in the performance of small diameter core drilling by facilitating a shearing mechanism of the composite workpiece through the utilisation of a novel tool design. This has been achieved by laser producing core drills from solid polycrystalline diamond, incorporating controlled cutting edges where the geometries are defined. To evaluate the efficiency of the shearing vs. abrasion/rubbing cutting mechanisms, a critical comparison between the novel (defined cutting edges) and the conventional electroplated tools (randomly distributed micro-grains) has been made with reference to thrust forces, tool wear mechanisms and their influences on the hole quality (e.g. delamination, fibre pullout). This work has been augmented by studies using high-speed thermal imaging of the two tool types in operation. The examinations have shown that, based on the concept of defined cutting edges in solid diamond, there is the possibility to make significant improvements in core drilling performance, (ca. 26% lower thrust force, minimal tool surface clogging, lower drilling temperatures) resulting in improved cleanliness of fibre fracture and a reduced tendency of material delamination. Highlights: A novel micro-core drill from solid PCD using defined edge geometries is presented. The PCD micro-core drill produces a shearing action in drilling carbon composite plate. A conventional electroplated diamond abrasive micro-core drill produces an abrasive/rubbing action. The drilling force produced by the diamond abrasive drill was 36% higher and temperature 11% higher than the PCD micro-drill. The shearing action of the PCD drill produces holes with superior edge definition and surfaces.